How does organizational stigma damage employees’ innovative performance? An emotional labor perspective - Guichuan Zhou; Kui Zheng; Anni Liu (Humanities & Social Sciences Communications)
Abstract In this rapidly developing and technologically advancing business environment, innovation has become crucial to an organization’s success. However, very few studies have explored the effect of organizational stigma, a negative label that becomes prevalent and situational in nature, on employees’ innovative performance. Using survey data from 151 employees in the overseas business departments of five Chinese multinational enterprises blacklisted by the U.S. government, along with one-on-one follow-up interviews with 17 participants, this study uncovers a psychological mechanism behind the negative relationship between organizational stigma and employees’ innovative performance. Specifically, organizational stigma prompts employees to engage in surface acting, which further leads to emotional exhaustion as employees are unable to replenish their emotional resources due to the negative experience of organizational stigma. This emotional exhaustion, in turn, diminishes the emotional resources employees can devote to innovative behaviors, resulting in a decline in their innovative performance. Moreover, this study identifies stigma attribution as a moderating factor, where employees who attribute stigma to positive appraisal-related causes experience a lesser decrease in their innovative performance. By combining quantitative surveys with qualitative interviews, this study not only helps bridge the gap in understanding the impact of organizational stigma at the relatively unexplored employee level, including its underlying mechanisms and boundary conditions, but also offers practical insights for managers on how to mitigate the negative effects of organizational stigma on employees’ innovative performance.